PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN MANUFAKTUR BALIETTE - Jonathan Irfon Hadi Wijaya; Yulia -; Christian Purnama (Jurnal Infra, 2013)
Baliette Manufacturing is a manufacturing company engaged in the manufacture and sales furniture in Jepara. The raw materials used come from suppliers from all over Indonesia. Baliette Manufacturing had problems in the profit and loss account, balance sheet calculation and determination of the volume of furniture.This application is created and developed by using Microsoft Visual Studio. Net 2005 and Microsoft SQL Server 2005 as the database storage. Applications are made to have the following scope: purchase, sale, payment of accounts payable, accounts receivable, accounting processes and financial statements include: general journal, purchases journal, sales journal, cash receipts and disbursements, payable reports, accounts receivable report, stock reports.The test results showed that the application can automatically process accounting directly related to the purchase and sales. Degree of accuracy, relevance, and completeness of the financial statements resulting applications reached 99%. Level of ease and application design reach 80%. While the benefits of the application get a grade of 100%.